2015
DOI: 10.1177/2055102915592090
|View full text |Cite
|
Sign up to set email alerts
|

Employee subjective well-being and physiological functioning: An integrative model

Abstract: Research shows that worker subjective well-being influences physiological functioning—an early signal of poor health outcomes. While several theoretical perspectives provide insights on this relationship, the literature lacks an integrative framework explaining the relationship. We develop a conceptual model explaining the link between subjective well-being and physiological functioning in the context of work. Integrating positive psychology and occupational stress perspectives, our model explains the relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
1
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 96 publications
1
35
1
7
Order By: Relevance
“…The settings in which one works – support at work, the nature of interactions and relationships with others, the work environment (Barling and Frone, 2004), and job characteristics (Warr, 2013) – all affect the well-being of an employee. SWB has been found to predict health and longevity of employment (Liu et al, 2010; Diener and Chan, 2011; Kuykendall and Tay, 2015; Tay et al, 2015), employees going beyond the call of duty for customers, lower turnover, and a lower intention of quitting (Podsakoff et al, 2007). Also, well-performing firms encourage positive affect (PA) in employees (Losada and Heaphy, 2004; O’Donohoe and Turley, 2006).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…The settings in which one works – support at work, the nature of interactions and relationships with others, the work environment (Barling and Frone, 2004), and job characteristics (Warr, 2013) – all affect the well-being of an employee. SWB has been found to predict health and longevity of employment (Liu et al, 2010; Diener and Chan, 2011; Kuykendall and Tay, 2015; Tay et al, 2015), employees going beyond the call of duty for customers, lower turnover, and a lower intention of quitting (Podsakoff et al, 2007). Also, well-performing firms encourage positive affect (PA) in employees (Losada and Heaphy, 2004; O’Donohoe and Turley, 2006).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Studies on subjective well-being and stress are also more focused on exploring the effect of stress on subjective wellbeing (Coyle, 2010;Hou & Liu, 2016;Kuykendall & Tay, 2015). However, Vazi, et al (2013) found that among the primary school teachers in East Cape, South Africa, their subjective and psychological well-being were able to predict stress significantly.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, such work will aid in identifying the areas upon which organizations should focus for facilitating physical health and sustainable "callings" for employees (e.g., sense of purpose; Schabram and Maitlis 2017). Again, integration with extant occupational health research, particularly with respect to physiological methodology "best practices" (e.g., see Eatough et al 2016;Ganster 2008;Semmer et al 2003) and existing frameworks linking physiology to work stressors, strains, and outcomes, will be helpful (e.g., Danna and Griffin 1999;Kuykendall and Tay 2015).…”
Section: Empirical Recommendationsmentioning
confidence: 99%